Anti-RNP Antibody: A Potential Novel Predictor for Osteonecrosis in Systemic Lupus Erythematosus - Xiong, Jiangbiao; Wang, Gang; Xu, Tian; Liu, Ren; Yu, Shujiao; Wang, Yan; Wu, Rui (Frontiers in Medicine, 2022)
Objective: To explore risk factors for developing osteonecrosis in patients with systemic lupus erythematosus (SLE). Methods: Twenty-six SLE patients with osteonecrosis from January 2018 to December 2019 were described. Fifty SLE patients without osteonecrosis were selected as controls from the SLE database (total 2680) of our hospital during the same period. Clinical manifestations and laboratory tests were recorded and analyzed, especially antibodies. Univariate and multivariate analyses were used to evaluate possible associated risk factors. Results: Twenty-six (3 male, 23 female) SLE patients with osteonecrosis were confirmed by X-ray and magnetic resonance imaging. The median course from SLE onset to osteonecrosis onset was 45 (range 2-302) months. Seven (27%) patients had a single joint involved and 19 (73%) patients had two or more joints involved. Besides, the incidence of femoral head osteonecrosis (FHON), knee ON, and humerus head ON were 85% (22/26), 27%(7/26), and 12%(3/26), respectively. The multivariate logistic regression analysis showed that the score of European Consensus Lupus Activity Measurement (ECLAM) at SLE onset [odds ratio (OR) 1.37; 95% confidence interval (CI) 1.07-1.75], a cumulative dose of prednisone above 10g (OR 15.49; 95% CI 3.38-84.61), and positive of independent anti-RNP antibodies (OR 3.35; 95% CI0.80-10.73) were significantly associated with osteonecrosis in SLE. Conclusion: The score of ECLAM at SLE onset, a cumulative dose of prednisone above 10g, and positive anti-RNP antibodies are associated with osteonecrosis in SLE. Herein, we reported for the first time that anti-RNP antibodies were associated with osteonecrosis in SLE patients and might be a novel predictor.